Interaksi Sosial Mahasiswa Universitas Pamulang Prodi PPKN dalam Menjaga Toleransi Antar Umat Beragama - Siti Aisah; Darto Wahidin (Journal on Education, 2025)
This study aims to analyze "Social Interaction of Pamulang University Students in Maintaining Tolerance Between Religious Communities". This study aims to social interaction of Pamulang University students in efforts to tolerance between religious communities. Social interaction is an important process in building reciprocal relationships, mutual understanding, and respect for differences. A qualitative approach with descriptive methods was used, through observation, interviews, and documentation studies of students between religious communities on campus. The results of the study indicate that student social interaction is reflected through ethical communication, interfaith relations, and academic and organizational activities involving various religious backgrounds. Supporting factors for tolerance include individual awareness, shared values, campus support, and inclusive academic experiences, while inhibiting factors are limited opportunities for interaction, differences in religious practices, and the lack of supporting facilities for interfaith activities. In conclusion, student social interaction plays an important role in building and maintaining tolerance, while requiring ongoing support from the academic environment to create a harmonious campus life.